1960
DOI: 10.1113/jphysiol.1960.sp006453
|View full text |Cite
|
Sign up to set email alerts
|

The function of the metanephros of foetal rabbits and pigs

Abstract: The mesonephros of foetal rabbits and pigs does not elaborate a fluid resembling urine (Stanier, 1960), analyses indicating that the fluid found in the bladder when the mesonephros is present resembles a protein-free filtrate of foetal serum. The function of the early definitive kidney (metanephros) has been investigated in a similar way; and since and Widdowson & McCance (1958) suggested that the chorioallantoic membrane may modify the composition of the fluid in the allantoic sac, this fluid has been compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

1960
1960
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 7 publications
0
10
1
Order By: Relevance
“…Thus, in the young rabbit, it takes between 3 and 4 weeks for the high rate of glycolysis of the renal cortex to fall to values found in the adult animal (Whittam, 1961). McCance & Stanier (1960) showed that the rabbit's foetuses, 9 days before term, and foetal pigs of 90 days gestation, excrete a urine which differs in its composition from the animal's own plasma and from the urine of the adult animal: its urea concentration is about three times that of the plasma, while its concentration of chloride (and presumably of sodium) is only half that of the blood serum. Nearly 30 years ago, McCance & Young (1941) demonstrated that the sodium and chloride clearance during the first 2 weeks of life of a baby were only about one fifth of those of adults, and that in the new-born in general the renal tubules reabsorb more of the sodium and chloride from the glomerular filtrate than adults do (McCance & Widdowson, 1953).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in the young rabbit, it takes between 3 and 4 weeks for the high rate of glycolysis of the renal cortex to fall to values found in the adult animal (Whittam, 1961). McCance & Stanier (1960) showed that the rabbit's foetuses, 9 days before term, and foetal pigs of 90 days gestation, excrete a urine which differs in its composition from the animal's own plasma and from the urine of the adult animal: its urea concentration is about three times that of the plasma, while its concentration of chloride (and presumably of sodium) is only half that of the blood serum. Nearly 30 years ago, McCance & Young (1941) demonstrated that the sodium and chloride clearance during the first 2 weeks of life of a baby were only about one fifth of those of adults, and that in the new-born in general the renal tubules reabsorb more of the sodium and chloride from the glomerular filtrate than adults do (McCance & Widdowson, 1953).…”
Section: Introductionmentioning
confidence: 99%
“…The anatomical relationships and connexions indicate, as has often been suggested, that the sac must act as a receptacle for the fluid secreted by the mesonephros and early metanephros, but the work of Stanier (1960), Crawford & McCance (1960) and McCance & Stanier (1960) indicates that the fluids passing into the sac from the bladder must be greatly modified during their storage there, probably by the chorioallantoic membranes. It still remains to be discovered just how the fluid is created in the early stages of foetal life and how its composition is altered by the active reabsorption of sodium, accompanied by chloride to some extent, and possibly with some simultaneous ionic exchange of sodium for hydrogen and other radicles.…”
Section: Physiological Significance Of the Ph Measurementsmentioning
confidence: 99%
“…The arterial blood pressure of the pig fetus increases during the second half of gestation (Macdonald, Llanos, Heymann & Rudolph, 1981;Macdonald, Colenbrander & Wensing, 1983) and concurrent with this there is a development in the competence of the kidney to retain electrolytes and water (McCance & Stanier, 1960;Alt, Colenbrander, Forsling & Macdonald, 1982). There is also evidence that the amount of renin in the fetal kidney increases over this period of gestation (Kaplan & Friedman, 1943), and that the plasma renin activity is high in the new-born piglet (Bailie, Derkx & Schalekamp, 1980;Osborn, Hook & Bailie, 1980).…”
Section: Introductionmentioning
confidence: 99%